Effect of excess silicate on the structure formation and textural properties of MTS materials - Inayat, Alexandra; Kuhnt, Andreas; Schwieger, Wilhelm; Einicke, Wolf-Dietrich; Kullmann, Jens; Enke, Dirk (Journal of Porous Materials, 2011)
The synthesis of micellar templated silica (MTS) materials has been conducted with different SiO2/CTAB molar ratios for two different cetyltrimethylammoniumbromide (CTAB) concentrations of 0.02 and 0.07 M to examine the structure formation for cubic (SBA-1) as well as for hexagonal (SBA-3) surfactant arrangement in acidic reaction medium with increasing silicate excess. Reaction products were analyzed with X-ray diffraction, N-2 physisorption and TG-MS. It was found that an increase of the silicate concentration leads to the formation of additional silica gel in the resulting MTS material, which causes not only a decrease of specific surface area and pore volume, but also of the mesopore diameter. The latter effect is explained by a proposed embedding theory. Furthermore, with increasing silicate content in the synthesis mixture a phase transformation from hexagonal to cubic pore arrangement was found for the CTAB concentration of 0.07 M and the maximum SiO2/CTAB molar ratio for ordered pore arrangement has been determined.
Keywords: Micellar templated silica (MTS); Silicate excess; SBA-1; SBA-3; Pore arrangement; Textural properties

Ethene/Ethane and Propene/Propane Separation via the Olefin and Paraffin Selective Metal-Organic Framework Adsorbents CPO-27 and ZIF-8 - Böhme, Ulrike; Barth, Benjamin; Paula, Carolin; Kuhnt, Andreas; Schwieger, Wilhelm; Mundstock, Alexander; Caro, Juergen; Hartmann, Martin; Hartmann, Martin (Langmuir, 2013)
Two types of metal-organic frameworks (MOFs) have been synthesized and evaluated in the separation of C-2 and C-3 olefins and paraffins; Whereas Co-2(dhtp) (=Co-CPO-27 = Co-MOF-74) and Mg-2(dhtp) show an adsorption selectivity for the olefins ethene and propene over the paraffins ethane and propane, the zeolitic imidazolate framework ZIF-8 behaves in the opposite way and preferentially adsorbs the alkane. Consequently, in break-through experiments, the olefins or paraffins, respectively, can be separated.

Thermal collapse of SAPO-34 molecular sieve towards a perfect glass - Wondraczek, Lothar; Gao, Guojun; Moencke, Doris; Selvam, Thangaraj; Kuhnt, Andreas; Schwieger, Wilhelm; Palles, Dimitrios; Kamitsos, Efstratios I. (Journal of Non-Crystalline Solids, 2013)
Controlled collapse of a silicoaluminophosphate molecular sieve CHA-type SAPO-34 by thermal aging was studied in a multi-method approach. Structural changes and the mechanism of order-disorder-order transitions during collapse were followed for varying annealing conditions between 1000 and 1100 degrees C. Collapse of SAPO-34 occurs via the formation of an intermediate amorphous state by the loss of long-range order but preservation to a high degree of short-range order and macroscopic morphology. This intermediate amorphous state with low entropy may be classified as a "perfect glass". Prolonged aging in the collapse regime results in the precipitation of crystalline AlPO4 while the SiO2 species initially remain in an amorphous phase. Further increasing the aging temperature leads to virtually complete recrystallization and, ultimately, melting. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Zeolite; SAPO-34; Collapse; Recrystallization; Thermal aging

Thermally Induced Growth of ZnO Nanocrystals on Mixed Metal Oxide Surfaces - Inayat, Alexandra; Makky, Ayman; Giraldo, Jose; Kuhnt, Andreas; Busse, Corinna; Schwieger, Wilhelm (Chemistry - A European Journal, 2014)
An in situ method for the growth of ZnO nanocrystals on Zn/Al mixed metal oxide (MMO) surfaces is presented. The key to this method is the thermal treatment of Zn/Al layered double hydroxides (Zn/Al LDHs) in the presence of nitrate anions, which results in partial demixing of the LDH/MMO structure and the subsequent crystallization of ZnO crystals on the surface of the forming MMO layers. In a first experimental series, thermal treatment of Zn/Al LDHs with different fractions of nitrate and carbonate in the interlayer space was examined by thermogravimetry coupled with mass spectrometry (TG-MS) and in situ XRD. In a second experimental series, Zn/Al LDHs with only carbonate in the interlayer space were thermally treated in the presence of different amounts of an external nitrate source (NH4NO3). All obtained Zn/Al MMO samples were analysed by electron microscopy, nitrogen physisorption and powder X-ray diffraction. The gas phase formed during nitrate decomposition turned out to be responsible for the formation of crystalline ZnO nanoparticles. Accordingly, both interlayer nitrate and the presence of ammonium nitrate led to the formation of supported ZnO nanocrystals with mean diameters between 100 and 400 nm, and both methods offer the possibility to tailor the amount and size of the ZnO crystals by means of the amount of nitrate.
Keywords: layered compounds; mixed metal oxides; nanoparticles; nitrogen oxides; zinc

Thermal stability studies of zeolites A and X synthesized from South African coal fly ash - Musyoka, Nicholas M.; Petrik, Leslie F.; Hums, Eric; Kuhnt, Andreas; Schwieger, Wilhelm (Research on Chemical Intermediates, 2015)
The thermal stability of zeolites A and X synthesized from coal fly ash was studied by evaluation of TGA-DTA curves obtained on increasing the temperature and by in-situ temperature-programmed XRD analysis. It was found that zeolites A and X were both stable up to approximately 800 A degrees C and retained their characteristic diffraction peaks up to 440 A degrees C, meaning the crystal structure was still stable. Of particular interest was that zeolite X, which has a unique hierarchical morphology, was thermally stable and was, hence, suitable for applications requiring elevated temperatures, for example catalysis and pollution control.
Keywords: Zeolites; Fly ash; Thermal stability; In-situ XRD